THE PERFORMANCE OF INFORMATION SYSTEM IN FACILITATING WORK COMMUNICATION BY ONLINE-BASED APPLICATION DURING COVID-19 PANDEMIC CRISIS - Keomorakath Pich; Wahyu Sardjono (Airlangga Journal of Innovation Management, 2020)
ABSTRACTThe business process needs an information system to support business activities, and it is working with technology. System information has developed small form functions to many functions that become parts of business need. Humans build a business and make activities in the business such as planning, practising, deciding, following, evaluating, controlling, and monitoring. Technology is essential for supporting and creating more solutions to build a business plan and division more completely. Communication is a part of business activities to have a good connection with employees, managers, and business partners. Recently, the pandemic of COVID19 influences everyone, business, economic, makes all in social distance or working from home. Nevertheless, it is not a big issue for humans anymore because technology has replaced humans' needs, and system information occurs to solve the business problem. This study proposes an analysis of the technology used in business management and system information on business in the present. In this research, the methodology analyzed secondary data to analyze and compare some digital communication platforms used by employees while working from home during COVID19 pandemic crisis. This study implies that there is an impact of system information to business and the increasing needs of the information system to support employee communication while working from home. Furthermore, even business needs technology and sophisticated information system; business still needs the human worker to control for business decision making in the future.  Keywords: Business process, Technology, Information System. ABSTRAKProses bisnis memerlukan sistem informasi untuk mendukung kegiatan bisnis dan bekerja dengan teknologi. Sistem informasi telah berkembang dari fungsi kecil ke banyak fungsi yang merupakan bagian dari kebutuhan bisnis. Manusia membangun bisnis dan membuat kegiatan dalam bisnis itu merencanakan, berlatih, memutuskan, mengikuti, mengevaluasi, mengendalikan, dan memantau. Teknologi adalah hal penting untuk mendukung dan membuat lebih banyak solusi untuk membangun rencana bisnis dan divisi secara lebih lengkap. Berkomunikasi adalah bagian dari kegiatan bisnis untuk memiliki koneksi yang baik dengan karyawan, Manajer, dan mitra bisnis. Bahkan ketika pandemi COVID19 berpengaruh bagi kinerja perusahaan, yang menyebabkan semua orang akan berada dalam jarak sosial atau bekerja dari rumah. Namun demikian, ini bukan masalah besar bagi manusia lagi, karena teknologi telah menggantikan apa yang dibutuhkan manusia dan sistem informasi dapat menjadi solusi yang dibutuhkan bisnis saat ini. Studi ini mengusulkan analisis teknologi yang digunakan dalam manajemen bisnis dan sistem informasi bisnis pada saat ini. Dalam penelitian ini, metodologi kualitas menggunakan data sekunder untuk menganalisis dan membandingkan platform komunikasi online yang digunakan karyawan ketika bekerja dari rumah dalam situasi pandemi COVID19 saat ini. Studi ini menyimpulkan bahwa meskipun pandemic member dampak bisnis dan sistem informasi dan teknologi menjadi kebutuhan bisnis yang urgen, bisnis, masih membutuhkan pekerja manusia untuk mengendalikan pengambilan keputusan bisnis di masa depan. Kata kunci: Proses Bisnis, Teknologi, Sistem Informasi